Efeitos neuroprotetores da curcumina durante o desenvolvimento de ratos submetidos à isquemia cerebra global - Lucetti, Elaine Cristina Pereira (2015)
The ischemic stroke precipitates a cascade of events that involve excitotoxicity, inflammation, oxidative stress and cell death. Curcumin has demonstrated neuroprotective effects, with antioxidant and antiinflammatory properties. Therefore, we aimed to study these effects of curcumin on experimental model of global cerebral ischemia in rats under development. Methods: Wistar female rats treatment began 24 hours after the birth of pups, during 21 days, with curcumin (25, 50 or 100 mg/kg/day, p.o.) or water + 1% Cremophor (10 ml/kg). In 21 day old rats were anesthetized with Ketamine (75 mg/kg, i.p.) and xylazine (10 m/kg, i.p.) and subjected to the global cerebral ischemia for 15 min, reperfusion at the same time, followed the left carotid cut. 24 h after surgery, pups started treating for 3 or 7 consecutive days. The animals treated for 7 days underwent behavioral tests, open field and water maze, to assess the locomotor activity and spatial memory, respectively. Groups of animals with 3 or 7 days after ischemia were sacrificed and the striatum, cortex and hippocampus were dissected. The striatum was used in homogenates preparation to monoamine and metabolites (DA, DOPAC, NS) dosing on HPLC. Homogenates from the hippocampus and cortex were prepared to test the antioxidant activity, 3 and 7 days post-ischemia, to nitrite and malondialdehyde (MDA) dosing. Hippocampal slices were separated for staining with Fluoro-Jade B and immunohistochemistry (iNOS, COX-2, TNF-). Results: Cerebral ischemia reduced the locomotor activity in rats and the treatment with curcumin reversed this effect; just like what happened with the special memory that was recovered after curcumin treatment in the three doses used. The striatum lesion reflected in a reduction in the levels of monoamines and these values were increased with the use of curcumin 3 and 7 days after surgery dose-dependent manner on day 3. MDA and nitrite levels were significantly increased in cortex and hippocampus, 3 and 7 days after global cerebral ischemia, when compared to the false-operated groups. The treatment with curcumin significantly protected these areas only at 3 days post-ischemia, in the doses of 50 and 100 mg/kg. On the 7th day, the best results were obtained with the dose of 25 mg/kg. Furthermore, there was a decrease in immunostained cells for iNOS, COX-2 and TNF- in treated groups with curcumin compared with ischemic group. As reduction Fluoro-Jade B positive cells. Conclusion: The previous treatment of the dams during the lactation period and the subchronic treatment of puppies with curcumin exerted neuroprotective properties against damage caused by global cerebral ischemia/reperfusion. These effects reflected improved in locomotor activity and memory. This activity was observed through anti-inflammatory and antioxidant actions of curcumin, especially three days after the ischemic event. These actions were confirmed with inhibition of COX-2, iNOS and TNF-. In addition, neurons were preserved in the hippocampus, which could be seen by staining with Fluoro-Jade B, viewed through green fluorescence.